2018
DOI: 10.1016/j.jrurstud.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Co-constructing sustainability: Agencing sustainable coffee farmers in Uganda

Abstract: This article explores the sustainability initiatives undertaken in a non-certified market involving an indigenous Southern firm and smallholder coffee farmers in Uganda. In response to recent calls, we take a performative approach to sustainability and employ an agencing lens to ask the question: how are sustainable coffee farmers constituted in concrete situations, and what role do they play in co-constructing sustainability? The ethnographic study undertaken reveals the proactive and interactive participatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
(101 reference statements)
0
12
0
4
Order By: Relevance
“…In recent years, examples of programs focused on soft skills and addressing social-cultural barriers to women's entrepreneurship have been emerging in countries ranging from Mexico to Zimbabwe. So far, however, these efforts have been sparse, carried out on small scale and not systematically (Onyas et al, 2018).…”
Section: Stylized Factsmentioning
confidence: 99%
“…In recent years, examples of programs focused on soft skills and addressing social-cultural barriers to women's entrepreneurship have been emerging in countries ranging from Mexico to Zimbabwe. So far, however, these efforts have been sparse, carried out on small scale and not systematically (Onyas et al, 2018).…”
Section: Stylized Factsmentioning
confidence: 99%
“…The sociology of market agencements is close in this respect to the studies that have shown the impacts of standards and labels (Raynolds 2009;Fouilleux and Loconto 2017) and the importance of distribution infrastructure (Ilbery and Maye 2005;Klein 2015) in alternative agri-food networks. However, in taking up the matter of materiality systematically, it also makes it possible to look at other market devices, the importance of which is less well known, such as packaging (Phillips 2016), charts of price lists (Henry 2017), displays urging farmers to save (Onyas et al 2018), and so on.…”
Section: The Sociology Of Market Agencements: a Theoretical Frameworkmentioning
confidence: 99%
“…This is particularly important for agricultural goods, which are biological entities characterized by great variety (Henry, 2017). Without standards for the generic characteristics of agricultural commodities or more specific qualities linked to one or the other option of sustainable agriculture, the large-scale trade in these commodities as we know it could not exist (Ouma 2015;Onyas et al 2018). Symmetrically, we might add, a failure to design new quality standards hobbles the development of a new market (Miele and Lever 2013).…”
Section: Six Marketization Processesmentioning
confidence: 99%
“…As Hagberg (2016) explains, 'agencing is a process in which agency is acquired and sustained by the continuous arranging of the elements of practices, accompanied by continuous adjusting of these elements in relation to other elements of the practices in which they are included' (p. 112). Similarly, Onyas, McEachern, and Ryan (2018), referencing Çalışkan and Callon (2010), describe the type of hybrid actors that emerge during processes of agencing as 'a composite consisting of heterogeneous elements including humans and (material and technical) devices which adjust to one another and act collectively' (p. 13). These quotes indicate that there is considerable 'adjusting' work involved in making agencing happen.…”
Section: Conceptualising Failures In the Agencing Of Consumersmentioning
confidence: 99%